Nest success and nest site selection of wetland birds in a restored wetland system - Auriel M. V. Fournier (Resilience Alliance, 2021)
Although most emergent wetlands across central North America have been destroyed or degraded, wetland restoration in recent decades has provided new habitat resources for wetland birds in agriculturally dominated landscapes. The goals of wetland restorations often include providing habitat for migratory and breeding waterfowl and other wetland birds. One such restored wetland complex in the Illinois River Valley, the Emiquon Preserve, is isolated from most flooding events of the Illinois River allowing the growth of persistent emergent vegetation that was quickly colonized by breeding wetland birds. We examined nest occurrence and variables influencing site selection, nest success, and changes in nest density across stages of the wetland succession cycle. We located 327 nests from nine species of wetland birds (American Bittern, Botaurus lentiginosus; American Coot, Fulica americana; Black-crowned Night-Heron, Nycticorax nycticorax; Black-necked Stilt, Himantopus mexicanus; Common Gallinule, Gallinula galeata; Green Heron, Butorides virescens; Least Bittern, Ixobrychus exilis; Pied-billed Grebe, Podilymbus podiceps; Sora, Porzana carolina) during 2013-2019. Common Gallinules were more likely to nest in persistent emergent vegetation than other cover types. American Coots and Least Bitterns selected nest sites based on water depth. Black-necked Stilt and Black-crowned Night-Heron nests were less successful in deeper water. Black-necked Stilt, Black-crowned Night-Heron, and Common Gallinule nests were less successful with later initiation dates. Nest density did not vary between persistent emergent and hemi-marsh cover types. Across 2013-2019 we estimated an average of 372 nests/year for six marsh-nesting bird species at Emiquon, including two state-endangered (Common Gallinule and Black-crowned Night-Heron) and one state-threatened (Least Bittern). Wetlands restored from agricultural fields can quickly provide critical breeding habitat for marsh-nesting birds of conservation concern, although continued management is needed to provide resources to maintain persistent emergent vegetation communities as individual marshes transition through the marsh cycle.